2011
DOI: 10.4067/s0718-58392011000400001
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Response of Watermelon to in-row Plant Spacings and Mycorrhiza

Abstract: Worldwide, a significant increase in watermelon (Citrullus lanatus [Thunb.] Matsum. & Nakai) growing areas has been registered in the last few years. In-row plant spacing has a significant effect on the growth and yield of watermelon, and can enhance competition for water and nutrients. The aim of this study was to investigate the effects of in-row plant spacing however, the fruit weight was not affected by mycorrhizal inoculation during early or total harvest. In this study, an in-row plant spacing of 1.0 m p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…decreased in low plant population probably due to the environmental factors including light, space, water and soil which are not optimally used (Cormark and Smith, 1998;Rassam et al, 2007) and the decrease in number of fruit per area at low population could be attributed to reduction in number of plants per hectare and this consequently, reduce the number of fruitful branches (Knavel, 1988;Walters and Schultheis, 2000). These results are in a good line with those reported by Shukla and Prabhakar (1987) on bottle gourd, Maynard and Scott, 1998 on muskmelon, Jan et al (2000) on bottle gourd, Kultur et al (2001), Goreta et al (2005), Ban et al (2006), Ban et al (2011) on watermelon, who reported that total yield and numbers of fruit per hectare were linearly increased with the increase in plant population.…”
Section: -Fruit Yield Characterssupporting
confidence: 88%
See 1 more Smart Citation
“…decreased in low plant population probably due to the environmental factors including light, space, water and soil which are not optimally used (Cormark and Smith, 1998;Rassam et al, 2007) and the decrease in number of fruit per area at low population could be attributed to reduction in number of plants per hectare and this consequently, reduce the number of fruitful branches (Knavel, 1988;Walters and Schultheis, 2000). These results are in a good line with those reported by Shukla and Prabhakar (1987) on bottle gourd, Maynard and Scott, 1998 on muskmelon, Jan et al (2000) on bottle gourd, Kultur et al (2001), Goreta et al (2005), Ban et al (2006), Ban et al (2011) on watermelon, who reported that total yield and numbers of fruit per hectare were linearly increased with the increase in plant population.…”
Section: -Fruit Yield Characterssupporting
confidence: 88%
“…Since competition between plants greatly affect yield (Thorenley, 1983;Willey and Heath, 1969) it is therefore possible to adjust size of the harvested crop to meet the requirements of the market by manipulating density (Cushman et al, 2004). Effect of plant density on the yield and its component in cucurbita crops (Ban et al, 2011;Abd el Hamed and Elwan, 2011;Babayee et al, 2012;Latifi et al, 2012;Baloch et al, 2013) were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Matsum. & Nakai [20], Musa acuminata Colla [21], and Prunus cerasifera L. [22]. In all these species, AMF improved plant growth parameters [10,[12][13][14][15]17] and the uptake of several major nutrients such as nitrogen and phosphorus in stressed conditions [23,24].…”
Section: Contribution Of Arbuscular Mycorrhizal Fungi To Plant Nutrition and Growthmentioning
confidence: 98%
“…Beneficial microbes are commonly used as inoculants for improving the growth and yield to replace chemical fertilizers, pesticides and supplements biological nitrogen fixing bacteria like "Azotobacter" to fix 180 & 10 6 metric tons/ year; Bacillus megatherium and B. circulans able to phosphate and potassium solubilizing, respectively; to stimulate plant growth, nutrition increasing the uptake of N,P K and Fe ; which they are rapidly colonize the rhizosphere, suppress soil borne pathogens at the root surface to control plant pests, produce metabolites e.g. antibiotics, phytohormones, volatile compounds, have efficient systems for uptake and catabolism of organic compounds in root exudate (Abou El Goud, 2006;Ban et al, 2011;Singh et al, 2012 andSoraya et al, 2020;). They able to act with soil beneficial microbes caused enhancable of microbial communities within rhizosphere, decrease the rates of chemical fertilizers (Abou El Goud, 2006) and increase the grain yield of Trigonella foenum and Nigella sativa.…”
Section: Introductionmentioning
confidence: 99%